Beyond Environmental Monitoring: Are Automatic Time-Lapse Cameras Efficient Tools for Temperature Measurement in Remote Regions? - Grenier, Jérémy; Decaulne, Armelle; Bhiry, Najat (SSRN Electronic Journal, 2023)
Automatic time-lapse cameras are frequently used to monitor snow and ice related slope processes on slopes in cold regions because of the many advantages they bring to researchers. In addition to providing important information about the dynamic of the studied area, most of these cameras are now equipped with thermal sensors able to register temperature data when every photograph is taken. The great instrumentation located within Tasiapik Valley, near Umiujaq, in Nunavik (northern Québec), enabled us to assess the potential of automatic time-lapse cameras for temperature measurement by comparing data retrieved on photographs with data from two nearby complete weather stations. Our results indicate that the temperature measurements taken by the time-lapse cameras from August to the onset of February are relatively accurate while the weaker performances occurred in late winter and spring (March-June). Moreover, regardless of the year, the time-lapse cameras were most accurate in the morning (09:00 AM-11:00 AM), while in the afternoon (12:00 PM-3:00 PM), they tended to overestimate temperatures. Based on our observation and data analysis, this over-estimation of air temperature seems to be caused by external factors such as the sky conditions and high values of daily mean downwelling that last from February to June. The environment near the cameras might also influence the performances at temperature measurement.